Pelatihan Pembuatanan Makanan Bergizi sebagai Upaya Pencegahan Stunting dan Budidaya Ikan Lele Dalam Ember sebagai Potensi Wirausaha Masyarakat - Ervan Hasan Harun; Arfan Utiarahman; Jumiati Ilham (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2022)
The Thematic of Kuliah Kerja Nyata (KKN) program carried out by LPPM UNG in this period carried the theme "Independent Campus for Villages: Village KKNT Builds for the Achievement of SDGs (Suistainable Development Goals)". The implementation of the Thematic Community Service Program this time is somewhat different from previous years, where in accordance with the Term of Reference (TOR) the Work Program or program topic is not determined, but students will develop a work program based on the results of the assessment of village needs and the results of coordination with the community and village government. Therefore, the theme of the activities that become the Core Program of KKN will only be known after students conduct field observations and assessments. Based on the results of the community needs assessment, it was found that the core programs in 2 (two) villages were the locations of the KKN (Posko) namely: 1). Karya Baru Village, Asparaga sub-district, Gorontalo district, are: Training on Making Nutritious Food as an effort to prevent Stunting, and 2). Olimohulo village, Asparaga sub-district, Gorontalo district, carries the core program of Catfish Cultivation in Bucket (BUDIKDAMBER) to the community. The implementation of the Thematic Community Service Program in Developing Villages has resulted in or can form: 1). Community groups that have awareness about the dangers of stunting; 2). Community groups who have the skills to make nutritious food with raw materials from agricultural products in the village; 3). Community groups who understand and are skilled in the field of catfish farming in buckets (BUDIKDAMBER); and 4). A new group of entrepreneurs in the field of freshwater fish farming